Spiritual Health among Nursing and Midwifery Students at Kerman University of Medical Sciences - Neda Rahimi; Esmat Nouhi; Nozare Nakhaee (Tehran University of Medical Sciences, 2014)
Background & Aim: The present study aimed to investigate the spiritual health among nursing and midwifery students at Kerman University of Medical Sciences in 2012 .   Methods & Materials: This was a cross-sectional study in which all 222 nursing and midwifery students studying at Kerman University of Medical Sciences were recruited to study. Data were gathered using t he Palutzian & Ellison questionnaire of spiritual well-being. The obtained data were then analyzed in the SPSS-20 using parametric statistical tests such as independent t-test and Anova .    Results: Results showed that spiritual well-being of nursing and midwifery students was in the good range. Except gender, no statistically significant relationships were observed between the mean of spiritual well-being and parameters such as age, marital status, academic year, and field of study .   Conclusion: According to the findings , spiritual health among nursing and midwifery students was moderate. It is necessary to promote spirituality among nursing and midwifery students .